Proton Pump Inhibitors Were Associated With Reduced Pseudocysts in Acute Pancreatitis: A Multicenter Cohort Study - Zhang, Shengyu; Han, Ziying; Zhang, Yuelun; Gao, Xiaomao; Zheng, Shicheng; Wang, Ruifeng; Wu, Dong (Frontiers in Pharmacology, 2021)
Background Acute pancreatitis (AP) is a systemic inflammatory disorder with a wide spectrum of clinical symptoms that can range from mild to severe. Previous preclinical study results suggest that proton pump inhibitors (PPIs) can inhibit exocrine pancreatic secretion and exert anti-inflammatory properties, which might in turn improve the outcome of AP. Aim We conducted this multicenter, retrospective cohort study to investigate the potential effects of PPIs on the mortality, total duration of hospital stay and local complication occurrence of patients with AP. Methods A total of 858 patients with AP were included. All patients presented to the hospital within 48 h of symptom onset and were divided into the following two groups: patients who were treated with PPIs (n=684) and those not treated with PPIs (n=174). We used propensity-score matching (PSM) analysis to reduce confounding bias before comparing the outcomes between the two groups. Results Before PSM analysis, there were significant differences in a number of parameters between the two groups, including age, sex, hematocrit, blood urea nitrogen, peritonitis signs, Ranson’s score, Acute Physiology Chronic Health Evaluation II score and organ failure occurrence. Before PSM, the PPIs group had a higher rate of mortality than the control group [RR=1.065; 95% confidence ratio (CI) 1.045-1.086; P=0.001]. After PSM, there was no significant difference in mortality (RR=1.009; 95% CI, 0.999-1.019; P=0.554) or total hospital stay (P=0.856), although the PPIs group had a lower occurrence of pancreatic pseudocyst (RR=0.416; 95% CI 0.221-0.780; P=0.005). Conclusions This study showed that PPIs therapy was not associated with reduced mortality or total hospital stay, but was associated with a reduction in the occurrence of pseudocysts in patients with acute pancreatitis.